PENGARUH KUALITAS PELAYANAN DAN FASILITAS TERHADAP LOYALITAS MELALUI KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING (Studi Kasus Hotel Truntum Padang) - Inayatul Husna; Myrza Rahmanita; Nurbaeti Nurbaeti; Fetty Asmaniati (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
The purpose of this study was to determine the effect of service quality and facilities on loyalty with customer satisfaction as an intervening variable at Truntum Padang Hotel. Research method is descriptive quantitative. Sampling technique uses purposive sampling method. The number of samples in this study amounted to 100 respondents. Data collection techniques using a questionnaire (questionnaire). Furthermore, data analysis uses SEM based on Partial Least Square. The results of this study indicate that service quality has a significant effect on customer satisfaction, facilities have a significant effect on customer satisfaction, customer satisfaction has a significant effect on loyalty, service quality has no significant effect on loyalty, and facilities have a significant effect on loyalty. The results of the test for the coefficient of determination show that the R Squre value simultaneously influences Z (Customer Satisfaction) of 0.457 with an Adjusted R Square value of 0.446, it can be explained that all independent variables (Exogenous) simultaneously affect Z (Consumer Satisfaction) by 44 .6%. The R Squre value has a simultaneous effect on Y (Loyalty) of 0.853 with an Adjusted R Square value of 0.848, it can be explained that all independent variables (Exogenous) simultaneously affect Y (Loyalty) of 84.8%.Keywords:Service Quality, Facility, Loyalty, Customer Satisfaction.